Disseminating and Using Student Assessment Information in Jordan - Obeidat, Osamha; Dawani, Zaina (World Bank, Washington, DC, 2014)
Student assessment has been increasingly recognized as playing a key role in monitoring and improving student learning and achievement levels. This case study discusses the important steps that Jordan has taken to strengthen its student assessment system and ensure that the information gathered from classroom assessments, examinations, and large-scale assessment activities supports student learning. Countries seeking to strengthen the utilization and dissemination of student assessment data can extract the following lessons from Jordan's experience: they should (i) set clear objectives for their assessment system, based on a well-defined vision of what is being assessed and why; (ii) entrust an external entity with managing system-level assessments in order to ensure impartial evaluation of the strengths and weaknesses of the education system; and (iii) introduce change gradually, coupled with adequate training on new assessment strategies and methods.